The five C's of cinematography : motion picture filming techniques - Mascelli, Joseph V. (Los Angeles : Silman-James Press, 1998)
Photographs, diagrams, and text help explain the essential concepts and techniques of motion picture camerawork.
Includes index.
Adult.
Adult
Keywords: Cinematography -- Handbooks, manuals, etc; Cinematography -- Handbooks, manuals, etc